Sensitisation to fish, crustaceans and molluscs in children with allergic conditions: clinical, laboratory and age-related features - Y.V. Marushko; B.L. Halushko; O.D. Moskovenko; A.I. Chmil (Zdorovʹe Rebenka)
Background. In recent decades, there has been a steady increase in the prevalence of food allergy among children, as well as the number of sensitised patients without clinical manifestations. Difficulties and possible risks in performing provocative tests necessitate the search for additional methods for the possible prediction of allergy to seafood and its clinical severity. In this context, the study of the dependence of clinical manifestations on age, source of sensitisation and levels of immunoglobulins is relevant. Objective: to study the prevalence of sensitisation to fish, crustaceans and molluscs in children depending on age and to determine the levels of total immunoglobulin E in them, taking into account age and clinical manifestations. Materials and methods. We examined 528 children aged 1 to 18 years with fish, crustacean and mollusc sensitivity using a molecular component enzyme immunoassay of venous blood on the ALEX2 test system (Macro Array Diagnostics GmbH, Austria). Food allergies were detected based on the EAACI 2023 guidelines. Results. Among the examined children undergoing allergy testing, the frequency of sensitisation to fish was 55.5 %, to crustaceans and molluscs — 36.3 %, and combined sensitisation was found in 8.5 % of patients. Seafood sensitisation was statistically significantly (p < 0.05) more common in children aged 4–6 and 7–12 years than in the age groups of 1–3 and 13–18 years. Participants with clinical manifestations of seafood sensitisation prevailed over patients without them, except for the age group of 7–12 years with sensitisation to crustaceans and molluscs. The examinees had higher levels of total immunoglobulin E in the presence of clinical manifestations. The most common symptoms were nausea, vomiting, difficulty breathing and urticaria, which occurred in 66.7–97.0 % of patients. Anaphylaxis in all sensitisation groups was detected in 12.1–14.8 % of cases. Conclusions. In children with sensitisation to crustaceans, fish and molluscs, peculiarities of clinical manifestations and the level of total immunoglobulin E were identified depending on age and source of sensitisation, which should be considered by clinicians when developing treatment and prevention measures.